Atomic spectrometry update: review of advances in the analysis of clinical and biological materials, foods and beverages. Issue 3 (21st February 2022) - Patriarca, Marina; Barlow, Nicola; Cross, Alan; Hill, Sarah; Robson, Anna; Taylor, Andrew; Tyson, Julian
Abstract : This review discusses developments in elemental mass spectrometry, atomic absorption, emission and fluorescence, XRF and LIBS, as applied to the analysis of specimens of clinical interest, foods and beverages. Sample preparation procedures and quality assurance are also included. Abstract : This update covers publications from the second half of 2020 to the middle of 2021. Advances in analytical techniques and their applications relevant to clinical and biological materials, foods and beverages are reviewed in the text, highlighting their key features. Three tables complement the text, aiming to summarise technical details of interest for sample preparation based on extraction procedures, applications to clinical and biological materials and analysis of food and beverage samples. In this year's review, we report on efforts to establish reference materials, reference procedures, reference networks and reference intervals, in some areas of clinical and food analysis. In terms of analytical developments, whereas ICP-MS and ICP-MS/MS are superior in their ability to achieve low LODs, there are also been an increase in the number of applications reporting sample pre-treatment involving SPE or LLE, to improve the LODs of poorer performing, but more affordable, techniques. Imaging is another expanding area, with several techniques being exploited to provide elemental profiles. Wider applications of instrumental developments, such as ICP-QQQ-MS and ICP-MS/MS, also provide analytical advantages in the area of clinical, food and beverages analysis and advances were reported. Authenticity and certification of origin are increasingly important features for certain food. Elemental profiling, coupled with statistical techniques, seems to be a very valuable tool to support these claims.